Macrophage migration inhibitory factor–CD74 axis drives vascular smooth muscle cell–induced M1 macrophage polarization to exacerbate intracranial aneurysm inflammation - Chen, Yao; Huang, Jian-huang; Wang, Qi-xiu; Song, Jian-hua; Chen, Jian-ning (Frontiers in Immunology, 2025)
BackgroundIntracranial aneurysms (IAs) develop and progress through pathological processes, including inflammation and abnormal changes in the vascular structure. The cytokine Macrophage Migration Inhibitory Factor (MIF) is implicated in the pathology of vascular diseases. However, the role of MIF in IAs remains to be elucidated.MethodsTranscriptomic data from IA and normal arteries were analyzed to quantify MIF expression and immune infiltration (CIBERSORT). Methylation sequencing assessed MIF promoter methylation. Single-cell RNA sequencing (scRNA-seq) defined secretory vascular smooth muscle cell (sVSMC) and M1-like macrophage proportions and MIF expression. Intercellular communication via the MIF-CD74 axis was evaluated using CellChat. In vitro functional experiments validated sVSMC-induced macrophage M1 polarization mechanisms.ResultsMIF mRNA was significantly upregulated in IAs (diagnostic AUC = 0.89) and correlated with increased M1-like macrophage infiltration (r = 0.783, p = 0.008). Hypomethylation of MIF was observed in IAs. scRNA-seq revealed expanded secretory VSMCs and M1-like macrophages, with elevated MIF in secretory VSMCs. CellChat confirmed enhanced MIF-CD74 signaling. In vitro, secretory VSMCs induced M1 polarization (iNOS/CD86↑, Arg1↓) via MIF-CD74; this effect was reversed by MIF knockdown or CD74 inhibition.ConclusionWe provide a comprehensive single-cell atlas of IAs and identify the sVSMC-derived MIF-CD74 axis as a novel mechanism driving macrophage M1 polarization and IA inflammation. This uncovers previously unrecognized sVSMC-macrophage crosstalk, establishing the MIF-CD74 axis as a promising immunomodulatory target for IA therapy.